2022
DOI: 10.1111/ssm.12541
|View full text |Cite
|
Sign up to set email alerts
|

Is science really for me? Gender differences in student attitudes toward science

Abstract: The question of whether single-sex or co-ed schooling has any impact on students' attitudes toward science is highly contested and warrants research from all corners of the world. This study adds to our current knowledge by investigating different attitudinal indices of Grade 9 science students (N = 356, M age = 14.5 years) in single-sex and co-ed schools in terms of involvement in science instruction, enjoyment of science, value of science, engagement in practical work, influences of family, teachers, peers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This concern has led researchers into a variety of studies that identified gender differences that could influence the number of girls in science and mathematics-related careers (Oakes, 2000). In the US, boys tend to hold more positive attitudes toward mathematics than girls (Kahle, 2003;Kurth, 2007) and this disparity in gender seems to prevail as pupils move from the primary school to the high school level (Kanai & Norman, 1997). Also in the US, Meyer and Koehler (1990) found gender disparities, favouring males, in students' self-confidence in learning mathematics, perceived usefulness of mathematics, perceptions of mathematics as a male domain and students' attributions to success or failure in mathematics.…”
Section: Resultsmentioning
confidence: 99%
“…This concern has led researchers into a variety of studies that identified gender differences that could influence the number of girls in science and mathematics-related careers (Oakes, 2000). In the US, boys tend to hold more positive attitudes toward mathematics than girls (Kahle, 2003;Kurth, 2007) and this disparity in gender seems to prevail as pupils move from the primary school to the high school level (Kanai & Norman, 1997). Also in the US, Meyer and Koehler (1990) found gender disparities, favouring males, in students' self-confidence in learning mathematics, perceived usefulness of mathematics, perceptions of mathematics as a male domain and students' attributions to success or failure in mathematics.…”
Section: Resultsmentioning
confidence: 99%
“…Several existing studies examined the impact of co-ed versus same-sex formal and informal STEM experiences. For example, Iwuanyanwu (2022) found that female students in single-sex schools had higher attitudes toward science than their counterparts in coed schools. Schilling and Pinnel (2019) found that single-sex engineering camps had a greater positive effect on female campers' self-efficacy through activities allowing campers to take risks, such as project-based learning (PBL) tasks.…”
Section: Gender and Stem Learning Environmentsmentioning
confidence: 99%
“…The Test of Science Related Attitudes Scale by Fraser was reduced (from 70 to 14 items) to suit elementary students. Based on gender, males outperform females in ATS in various places, such as in Africa (Iwuanyanwu, 2022), Hong Kong (Ma, 2022), Hungary (Szalkay et al, 2021), Spain (Toma et al, 2019). However, ATS literature on gender is still limited and an unresolved issue (Mao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%